AN AUTOPSY BASED STUDY OF ADRENAL GLANDS IN MEDICOLEGAL CASES (Journal of Forensic Medicine & Toxicology, 2019)
Adrenal glands are rarely observed for any pathology or trauma during routine medico-legal autopsy. As such they are small in sizes and enclosed within renal fascia, thus avoid routine post-mortem dissection as forensic pathologist never tried to link them either with cause of death or contributory cause of death. Though clinician based upon deteriorating signs and symptoms of the patient, may able to diagnose adrenal pathology that leading to adrenal insufficiency through biochemical or radiological investigations, forensic pathologist rarely bothers to explore that aspect, both in traumatic death as well as sudden death. In the present autopsy based study, adrenal pathology could be detected in (15.20%) cases out of total 250 cases. Macroscopically, haemorrhage, fragility and infarction of the adrenal glands were observed mostly whereas during histopathology, cortical haemorrhage and vascular contestation of the adrenal glands were observed mostly. The present study was an attempt to highlights the importance of observing adrenal glands for any trauma or pathology during routine medico legal autopsy so that proper cause of death or contributory cause of death can be concluded. This may also help to reduce the incidence of obscure or negative autopsy.
Keywords: Autopsy; Adrenal pathology; Adrenal insufficiency; Trauma; Adrenal haemorrhage; Cause of death.